Shinni ma Shomi kan Kerfotagha’, a Kushi story - Batic, Gian Claudio (AAeO - Afrikanistik-Aegyptologie-Online, 2017)
Kushi is a minority Chadic language spoken in northeastern Nigeria. This article presents an oral text known as Shinni ma Shomi kan Kerfotagha (‘The story of Shomi and Kerfotagha’), a folktale depicting the adventures of Shomi, the Kushi trickster par excellence. The text is accompanied by word-by-word interlinear analysis and by an English translation.